Sitios de geodiversidade do Município de Salitre, Chapada do Araripe. - Oliveira, Tereza Mara de (2018)
The elaboration of this work aimed to identify and quantify the geodiversity values and the areas of occurrence in the municipality of Salitre, seeking to support the actions of geoconservation in these places. With the inventory, it was verified that the studied area has five sites classified in local relevance level (Morro da Cruz, Morro do Chapéu, Baixio do Mocó, Quaternário and Pedra do Convento) and a site with the potential to become a geosite of regional relevance (Paleotoca). It is suggested to use geoconservation tools in the sites in Salitre to safeguard them for generations to come, through sustainable use for geotourism and scientific use.